Knowledge, attitude, and proficiency of healthcare providers in cardiopulmonary resuscitation in a public primary healthcare setting in Qatar - Veettil, Shajitha Thekke; Anodiyil, Mohamed Shaheen; Khudadad, Hanan; Kalathingal, Mohamed Ali; Hamza, Abdul Hakeem; Ummer, Femina Purakaloth; Alnuaimi, Ahmed Sameer (Frontiers in Cardiovascular Medicine, 2023)
Introduction Early and effective cardiopulmonary resuscitation (CPR) increases both survival rate and post–cardiac arrest quality of life. This study aims to assess the current knowledge and ability of physicians and nurses in health centers (HCs) operated by the Primary Health Care Corporation (PHCC) in Doha, Qatar, to perform CPR. Methodology This study consists of two parts. The first part is a descriptive cross-sectional survey using an online form targeting physicians and nurses working in all HCs to assess their CPR knowledge and attitude. The second part is a direct observation of CPR drills to evaluate the skills and competencies of code blue team members in a convenient sample of 14 HCs. A multivariate model was employed to test the independent effect of explanatory variables on the total knowledge score. Results A total of 569 physicians and nurses responded to the survey. Only one-half (48.7%) formally received training on basic life support within the last year. Furthermore, 62.7% have tried to revive a dying person with no pulse. All the participants recognize the importance of knowing how to revive a dying adult or child as part of their job. The study showed that being a nurse was the most important predictor of a higher knowledge score in both components. Attending more resuscitation courses (3–6 courses in the last 3 years) ranked second in importance, and a longer experience in clinical practice (5–10 and >10 years) ranked third in predictive power. In addition, the direct observation of CPR drill performance revealed a satisfactory outcome. Conclusion The level of CPR knowledge and skills practice among healthcare providers in PHCC is deemed satisfactory as most providers reported having performed CPR in the past. Considering that PHCC is the first step to people’s healthcare in Qatar, clinical staff should be certified and assessed regularly to ensure retention of resuscitation knowledge and skills.